Skills, knowledge, and implementation of techniques for behavioral guidance in adults with a fear of dentistry - Wagisha Barbi; Vaibhav Raj; Mehdi Askari; Toshi Toshi; Dipti Gopalakrishnan; Khushboo Kumari; Priyadarshini Rangari (Wolters Kluwer Medknow Publications, 2021)
Background: Dental fear and anxiety (DFA) is considered the main reason of dental negligence which can lead to detrimental oral health as well as overall health including psychological well-being and quality of life in an individual. Aims: The present trial was aimed to assess the skill and knowledge of dentists in managing DFA in adult subjects, to evaluate the available strategies used in treating such subjects, and to find the need for further education. Materials and Methods: The present study was an original survey and questionnaire trial, which was distributed to the 82 dentists. The collected data were subjected to statistical evaluation and the results were formulated. Results: Educating and motivating subjects was found to be effective by 62.19% (n = 51) of dentists followed by successive approximation, and muscle relaxation was considered highly ineffective by one responder (1.21%). Music and reduced waiting time in the clinic appeared to be the most effective strategy as responded by 56.09% (n = 46) of dentists. Attempting treatment in various visits than a single seems to be a highly ineffective technique by 4 dentists (4.87%). Conclusion: Within its limitation, the study showed that the application of various behavior modification techniques can be effective in alleviating DFA in adult patients.